The contributions of scholars to the definition of weapons and the spread of military awareness during the conquest of Oran II in the year 1792 in the light of local sources - Boudjellal, kadour (The Algerian Historical Journal, 2026)
During The Spanish colonisation of Oran, scholars diden’t only take into considiration to call far Djihad or holly war withe out taking any actions, since actions speak londer than words they were never far a way from battle fields. They were the first to translate their words to actions So That to Mak their invoction into concrete mauners Scholars. We shall try in the following pages to maintain all the efforts of scholars and students to reconquer Oran and to clanfy the region specily the bay Mohammed El Kbir had all his trust on them (Scholars) to create a long term emborgo against the spanish he settled them on senstive